Spotted Wing Drosophila (Drosophila suzukii): Identification, Ecology, and Management - Lindsy Iglesias; Teresia W. Nyoike; Oscur E. Liburd (EDIS)
Spotted wing drosophila (SWD) is a tiny invasive fruit fly pest of small fruits. It has been found infesting fruits in Europe and North and South America. Since its first capture in California in 2008, SWD has established populations throughout the United States in over 47 states. This trifold brochure describes how to identify and monitor these tiny pests and explains a few strategies to control them and limit the damage they cause to fruit crops. Written by Lindsy Iglesias, Teresia W. Nyoike, and Oscar E. Liburd, and published by the Entomology and Nematology Department, December 2015.